THE EFFECT OF HUMAN RESOURCES, BUDGET PARTICIPATION, AND LEADERSHIP STYLE ON THE QUALITY OF INFORMATION ON THE FINANCIAL AND INTERNAL CONTROL AS MODERATION VARIABLES (A Case Study on Takalar City Goverment) - mas uleng (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2019)
This study aims to analyze human resources on the quality of information, budget participation on the quality of information, leadership style on the quality of information, human resources on the quality of information through internal control as a moderating variable, budget participation on the quality of information through internal control as a moderating variable, to the quality of information through internal control as a moderating variable.            This study uses a quantitative approach by testing the hypothesis (hypothesis testing) to see the correlation that occurs between the Budget Participation, And Leadership Style To The Quality Of Information Financial Statements And Internal Control As Moderation Variables. The object of this research is head section, head of department, and head of OPD district of Takalar. Data collection techniques used questionnaires survey method with OPD was 140 respondents with purposive method. Data analysis technique used is Partial Least Square (PLS) approach with Smart Software PLS 3.0.            The results of this study show that human resources affect the quality of information on local government financial statements while budgetary participation does not affect the quality of information on local government financial statements and leadership style also has no effect on the quality of local government financial report information but internal controls can moderate the relationship of human resources and the quality of local government financial statements information significantly Internal controls are not able to moderate the relationship of budget participation and the quality of information on local government financial statements significantly Internal controls are able to moderate the relationship of leadership style and quality of information on local government financial statements significantly.Keywords: Human Resources, Budget Participation, Leadership Style, Budget Participation,  Quality Information, Internal control.